Plant-Derived Polysaccharides as Modulators of the Gut–Liver Axis in Metabolic Dysfunction-Associated Steatotic Liver Disease - Meartinos Reamos; Henrik R. Baker (International Journal of Clinical and Translational Medicine, 2026)
Metabolic dysfunction-associated steatotic liver disease (MASLD) has emerged as a global health challenge, driven by intertwined dietary, microbial, and host metabolic perturbations. The gut–liver axis constitutes a bidirectional communication system whose architecture integrates intestinal barrier integrity, microbial ecology, bile acid signaling, and immune surveillance. Within this complex adaptive system, plant-derived polysaccharides exhibit a striking capacity to orchestrate multi-level modulatory effects that extend far beyond their traditional classification as dietary fibers. This paper presents a systems-level analysis of how structurally diverse polysaccharides interface with the gut–liver axis, emphasizing architectural trade-offs, network robustness, governance of physiological boundaries, and deployment considerations. Rather than cataloging molecular interactions in isolation, we characterize the gut–liver axis as a layered infrastructure with modular functional units, feedback regulation, and emergent properties that determine resilience against steatotic insults. Plant polysaccharides are positioned as soft modulators that engage multiple nodes simultaneously, enabling context-dependent reconfiguration of microbial consortia, reinforcement of epithelial barrier architecture, and tuning of hepatic inflammatory and metabolic circuits. The discussion extends to structural trade-offs among polysaccharide complexity, fermentability, and site-specific activity, highlighting how source-dependent molecular topologies influence system-level outcomes. Further, we examine the infrastructure required for scalable production, standardization, and equitable deployment of polysaccharide-based interventions, addressing sustainability of raw material supply chains and regulatory governance challenges that straddle the boundaries between food, supplement, and therapeutic agent. By reframing polysaccharide action through the lens of systems architecture and policy, this analysis reveals the deep coupling between molecular design, ecological resilience, and societal implementation that must be navigated to translate gut–liver axis modulation into population-wide metabolic health benefits.